A comparative study of single-stage bilateral vs. unilateral medial unicompartmental knee arthroplasty on complications, clinical outcomes, and costs - Tu, Kao-Chang; Shih, Han-Ting; Wang, Shun-Ping; Chen, Kun-Hui (Frontiers in Surgery, 2024)
BackgroundThis retrospective study aimed to evaluate the short-term recovery and cost-effectiveness of bilateral unicompartmental knee arthroplasty (UKA) compared to staged unilateral UKA. The study analyzed postoperative pain scores, medical costs, and complications in patients with knee osteoarthritis who underwent these procedures.MethodsA total of 226 patients who received either unilateral UKA (Group A, n = 170) or bilateral UKA (Group B, n = 56) using the mobile-bearing UKA were included in the study. Patient demographics, surgical details, postoperative pain scores, knee range of motion, length of hospital stay, self-controlled analgesic use, total medical costs, and complications were retrospectively collected from medical records.ResultsThe demographic characteristics were comparable between the groups. Group B had a longer surgical time and higher medical costs than Group A. However, there were no significant differences in hospital stay, pain scores, or knee range of motion between the two groups. Complications were infrequent and not significantly different. Insert dislocation and loosening were the most common complications. Patient-controlled analgesia effectively reduced pain scores in Group A but not in Group B.ConclusionBilateral UKA does not significantly affect hospital stay, postoperative pain, or complications compared to unilateral UKA. Although bilateral UKA requires longer surgical time and incurs higher costs, it offers the potential benefit of reducing anesthesia-related complications and overall health insurance expenditures. This study recommends bilateral UKA as a suitable option for patients with bilateral knee osteoarthritis, given its comparable short-term outcomes and potential cost-saving advantages.Level of EvidenceIII